USE OF MORPHOLOGICAL MARKERS TO IDENTIFY FOLIAR DISEASE RESISTANCE IN GRAPEVINE - Z. Gökbayrak; C. Özer; G. Söylemezoğlu (Journal of Animal and Plant Sciences, 2010)
Morphological characteristics of 324 vines, developed from a cross between ‘Italia’ and ‘Mercan’ grapevine varieties with various levels resistance to powdery and downy mildew were examined for a possible association with disease resistance  using a tree-based discriminant analysis. Petiole coloration was the main discriminant for downy mildew. When the pigmentation was low, anthocyanin coloration of the tip was needed to screen susceptible plants from the resistant ones. With the anthocyanin pigmentation medium to strong, 63.5% of the plants were selected as resistant. Plants with darker petiole color required mature leaf profile and width of the petiolar sinus to be factored in to successfully discriminate the susceptible ones from the resistant plants. Anthocyanin coloration of the tip was the main discriminant variable for powdery mildew. Alongside of a strongly colored shoot tip, the petiole color and the shape of the mature leaf blade had to be incorporated into selection process.  It seems that anthocyanin in petioles or shoot tip might play a role selecting resistant or susceptible genotypes from the population.
Keywords: grapevine; fungal disease; classification tree analysis; vegetative traits; anthocyanin.